A Passive Radar System for Monitoring of Coastal Areas Ship Traffic Using Satellite Illumination Signals - Nguyen Van Quan (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Increasing requirements for improving of information systems for ensuring navigation safety in coastal areas of marine waters determine the search of new engineering and scientific solutions. The creation of a passive coherent location systems (PCL), based on existing sources of electromagnetic radiation (in particular, global navigation satellite system (GNSS) signals) as radar illumination of the monitored space is of particular interest. During development and implementation of the systems, there are a number of problems related to the search of highly efficient processing algorithms, to the optimization of structure and functioning modes when the system is a part of a complex multi-position monitoring system in coastal areas. Aim. Rationale of the structure of bistatic PCL system with GNSS illumination signal, analysis of methods for increasing of the level of reflected signals, development of a general signal processing algorithm of the system receiver unit, formation of proposals for the creation of multi-position radar system (MP radar) for coastal areas navigation monitoring. Materials and methods. Mathematical modeling, theory of signals, methods of digital signal processing. Results. The structure of the bistatic PCL with GNSS illumination signal for monitoring in coastal areas of marine waters to ensure navigation safety has been developed. Methods for increasing the power level of satellite signals at the input of the receiving device have been proposed. General signal processing algorithm and the algorithm of CAF calculation in the bistatic PCL system using GPS C/A code satellite signal for sea surface coastal areas monitoring have been developed. Conclusion. The considered bistatic PCL system with GNSS illumination may be applied as a part of MP radar for monitoring in areas of heavy vessel traffic to ensure the safety, for operational control of marine operations in the high seas, for quick analysis of the situation at sea in an emergency.